140k views
5 votes
Find the inverse function of h(x) = -2/3x + 6.

User DraxDomax
by
5.6k points

2 Answers

4 votes

Answer:


x=-(3)/(2) x+9

Explanation:

We are given the following function and we are to find the inverse of this function:


h(x) = - \frac { 2 } { 3 } x + 6

For that, we will put the function equal to another variable
y and make
x the subject of the function.


y = - \frac { 2 } { 3 } x + 6

Making
x the subject:


y-6=-(2)/(3) x


3(y-6)=-2x


(3y-18)/(-2) =x


x=-(3)/(2) x+9

Therefore, the inverse h'(x) =
x=-(3)/(2) x+9.

User Wspeirs
by
5.9k points
5 votes

Answer:


h^(-1)(x)=-(3)/(2)x+9

Explanation:

To find inverse of a function, follow the steps below:

1. replace h(x) with y

2. Interchange x and y

3. Solve for the new y

4. Replace y to
h^(-1)(x) (this is the inverse function)

Step 1: y = -2/3x+6

Step 2: x = -2/3y+6

Step 3:


x=-(2)/(3)y+6\\(2)/(3)y=-x+6\\y=(-x)/((2)/(3))+(6)/((2)/(3))\\y=-(3)/(2)x+9

Step 4:


y=-(3)/(2)x+9\\h^(-1)(x)=-(3)/(2)x+9

This is the inverse function.

User Hackonteur
by
5.5k points